Grain size influence on the flexibility and luminous intensity of inorganic CaTiO3:Pr3+ crystal nanofibers. Issue 22 (15th November 2021) - Wang, Dehua; He, Hongwei; Wang, Xiaoxiong; Yu, Yang; Jiang, Longlong; Lu, Ye; Yu, Jing; Zhang, Jun; Long, Yunze; Ruan, Keqing
Abstract: Traditional inorganic materials exhibit rigidity owing to the lack of polymer chains in polymer materials or atom slipping in metals. However, nanometerization has been recently proposed for the conversion of inorganic oxide materials into flexible materials. Herein, the flexible inorganic luminescent material, CaTiO3 :0.2%Pr 3+, was synthesized through electrospinning, and the macroscopic flexibility of pure inorganic CaTiO3 :0.2%Pr 3+ was achieved. The flexible membrane was characterized via X-ray diffraction, thermogravimetry, scanning electron microscopy (SEM), and photoluminescence analyses. The grain size was analyzed at various calcination temperatures via SEM, and the results suggested that the increase in the calcination temperature resulted in the growth of crystal grains. Studies have reported that the growth of crystal grains is beneficial for improving the luminescence performance; however, to obtain better flexibility, smaller crystal grains are required. This study provides an important reference for the design of flexible inorganic materials.